Modelling and Simulation of Three Level Inverters for Main Drive of the Plate Mill Rolling Stand - Gasiyarov Vadim R.; Radionov Andrey A.; Maklakov Alexander S. (MATEC Web of Conferences, 2016)
This paper addresses a modelling and a simulation of three level inverters for main drive of the plate mill rolling stand. The main purpose of the article is to develop of a mathematical description of the three level voltage source inverter based on a space vector pulse width modulation and to simulate a consumption current by the main electric drive based on 18-pulse rectification circuit. A twelve-megawatt synchronous motor as a load has been used. The modelling results were simulated at the Matlab/Simulink program. It can allow us to estimate an electromagnetic compatibility of the main electric drive based on transients of the consumption current. The research results can be used to assess the electromagnetic compatibility of powerful three level natural point clamped converters with different types of the space vector pulse width modulation on a load or a grid.